The Dilemma of the Clinical Utility of Alzheimer Biomarker Evaluation in Everyday Clinical Practice: My Favorite PETs. (17th January 2023) - Beversdorf, David Q.; Scharre, Douglas W.
Abstract : Accurate diagnosis and early identification of neurodegenerative conditions lead to more specific treatment options and potentially improved outcomes. For those patients with cognitive complaints, it can be just as important to identify those who do have neurodegenerative causes of decline as those who do not. In the past, the diagnosis of Alzheimer disease (AD) had been made through careful clinical evaluation, without the use of fluid biomarkers or PET neuroimaging, where a characteristic onset of symptoms typical of AD and lack of features suggestive of other diseases, would lead to a clinical diagnosis of probable AD. 1 Certainty about the diagnosis was only obtained when there was pathologic examination of the brain tissue itself.